Motivations and Barriers in Slum Relocation: A Case Study of Dharavi in Mumbai - Singhi, Neha; Rutherford, Peter (MAJ - Malaysia Architectural Journal, 2025)
The sustainability of an urban environment is not just limited to its ecological footprint; it encompasses ecological, social, and economic dimensions. In urban environments worldwide, a peculiar phenomenon is observed: the hesitation of slum dwellers to relocate to what are presented as superior living conditions. Using Mumbai's Dharavi as a case study this study delves deep into understanding this reluctance. The introduction of a 'top-down' developmental approach, by the local government, has been met with resistance spanning two decades, the protests and resistance highlight the disconnect between policy formulations and ground realities and the resilience of a community that has witnessed multiple eviction attempts. This research juxtaposes Dharavi residents' current living conditions against proposed relocation models, employing Maslow's hierarchy of needs as a framework. The objective is to unveil the multi-faceted reasons - social, cultural, psychological, and economic - that anchor to its familiar habitat. Understanding a slum is not about viewing it as a monolithic entity of poverty and decay. It's about comprehending its intricate dynamics: the small businesses running from homes, the community ties that provide a safety net, the cultural norms that guide daily interactions, and the psychological aspects of familiarity and identity. Hence merely providing improved structural facilities is not enough to motivate them to relocate. The cultural, and socioeconomic dimensions that shape the lives of its residents must be addressed. The true essence of redevelopment should encompass strategies that not only offer better living conditions but also resonate with the intrinsic needs and aspirations of its dwellers. Only then the resident’s transition can see the new space not just as a dwelling but as a true home.